The formulation of lozenge using black mulberries (Morus nigra L.) leaf extract as an α-glucosidase inhibitor - Arif Budiman; Ferry F Sofian; Ni Made W S Santi; Diah L Aulifa (Wolters Kluwer Medknow Publications, 2020)
Background: Diabetes mellitus is a chronic metabolic disease, which possibly leads to kidney, brain, heart failure, and other organ complications, subsequently harming human health. These symptoms have been prevented using the leaf of black mulberry (BM), as a traditional medicine, because the phenolic compounds contained are able to decrease blood glucose concentration. Meanwhile, previous reports have shown that BM contains 1-deoxynojirimycin, with strong activity as an α-glucosidase inhibitor. The aim of this study, therefore, was to formulate and evaluate BM leaf extract in lozenge dosage form as an α-glucosidase inhibitor. Materials and Methods: The leaves of BM were extracted using the maceration method, where ethanol (70%) served as a solvent, and the inhibitory activity of the sourced α-glucosidase enzyme was determined through in vitro study. Subsequently, the extract was formulated into lozenge dosage form and evaluated for physical stability and also the effect of α-glucosidase enzyme. Results: The result showed an inhibitory activity of BM leaf extract against the enzyme α-glucosidase, with a half maximal inhibitory concentration (IC50) value of 357.6 μg/mL, whereas the lozenge formulation containing 43% of extract as well as 5% polyvinylpyrrolidone showed the best physical stability as compared to other formulas. However, the lozenge inhibits α-glucosidase enzyme with an IC50 value of 549.7 μg/mL. Conclusion: It was established that the lozenge of BM leaf extract possesses activity as an α-glucosidase inhibitor.